IL-27 regulation of innate immunity and control of microbial growth - Jessica M Povroznik; Cory M Robinson (Future Science OA, 2020)
IL-27 is a pleiotropic cytokine capable of influencing both innate and adaptive immune responses. With anti- and pro-inflammatory activity, IL-27 exerts its opposing effects in a cell-dependent and infectious context-specific manner. Upon pathogenic stimuli, IL-27 regulates innate immune cells, such as monocytes, dendritic cells, macrophages and neutrophils. Immune responses involving these innate cells that are negatively regulated by IL-27 signaling include inflammatory cytokine production, phagolysosomal acidification following phagocytosis, oxidative burst and autophagy. IL-27 signaling is crucial in maintaining the subtle balance between Th1 and Th2 immunity, in which protective inflammation is upregulated within the early stages of infection and subsequently downregulated once microbial growth is controlled. The immunomodulatory effects of IL-27 provide promising therapeutic targets for multiple disease types.